2015
DOI: 10.1002/hep.27941
|View full text |Cite
|
Sign up to set email alerts
|

The empirical antibiotic treatment of nosocomial spontaneous bacterial peritonitis: Results of a randomized, controlled clinical trial

Abstract: Spontaneous bacterial peritonitis (SBP) is a common, life-threatening complication of liver cirrhosis. Third-generation cephalosporins have been considered the first-line treatment of SBP. In 2014, a panel of experts suggested a broader spectrum antibiotic regimen for nosocomial SBP, according to the high rate of bacteria resistant to third-generation cephalosporins found in these patients. However, a broader-spectrum antibiotic regimen has never been compared to third-generation cephalosporins in the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
192
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(210 citation statements)
references
References 32 publications
9
192
2
3
Order By: Relevance
“…
Altogether, our preclinical data on B-cell depletion (4) and published data in AIH patients (1) suggest that prospective studies using anti-CD20 as initial therapy to induce remission in patients with AIH are indicated. These studies will be able to provide safety profile and design tailored protocols for different subtypes of AIH patients, including those with other comorbidities.
…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…
Altogether, our preclinical data on B-cell depletion (4) and published data in AIH patients (1) suggest that prospective studies using anti-CD20 as initial therapy to induce remission in patients with AIH are indicated. These studies will be able to provide safety profile and design tailored protocols for different subtypes of AIH patients, including those with other comorbidities.
…”
mentioning
confidence: 81%
“…(1) Hassan et al screened for invasive fungal infection in 46 end-stage liver disease (ESLD) patients from the intensive care unit: both blood and ascitic fluid samples were collected for fungal culture and polymerase chain reaction.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Arányuk az elmúlt néhány évben fokozatosan nő, egyes tanulmányokban már meghaladta a GNB-két [24,25]. Nosocomialis infekciók esetén a GPB-k aránya 63% körül van [26]. A GPB-k irányába történő eltolódást legalább részben a nosocomialis és egészségügyi ellátáshoz kötötten megjelenő SBP-k gyakoribbá válása magyarázza.…”
Section: áBraunclassified
“…When nosocomial SBP is diagnosed, the European Association for the Study of the Liver guidelines recommend piperacillin/tazobactam or meropenem 6 a glycopeptide 11 ; however, the first randomized prospective 2-center clinical trial from Italy has shown superior outcomes with meropenem 1 daptomycin compared to ceftazidime. 20 Repeat paracentesis is not absolutely required. However, if clinical improvement is lacking, or relisting for transplant is desired, confirming a PMN count decrease of 25% in 48 hours or at a later time point an absolute PMN count of <250 cells/mm 3 indicates resolution.…”
Section: Spontaneous Bacterial Peritonitismentioning
confidence: 99%